Mitochondrial Carrier Homolog 2 Functionally Co-operates With BH3 Interacting-Domain Death Agonist in Promoting Ca2+-Induced Neuronal Injury - D’Orsi, Beatrice; Niewidok, Natalia; Düssmann, Heiko; Prehn, Jochen H. M. (Frontiers in Cell and Developmental Biology, 2021)
The BH3 interacting-domain death agonist (BID) is a pro-apoptotic member of the Bcl-2 protein family. While proteolytic processing of BID links death receptor-induced apoptosis to the mitochondrial apoptosis pathway, we previously showed that full length BID also translocates to mitochondria during Ca2+-induced neuronal cell death. Moreover, mitochondrial carrier homolog 2 (MTCH2) was identified as a mitochondrial protein that interacts with BID during cell death. We started our studies by investigating the effect of Mtch2 silencing in a well-established model of Ca2+-induced mitochondrial permeability transition pore opening in non-neuronal HCT116 cells. We found that silencing of Mtch2 inhibited mitochondrial swelling and the associated decrease in mitochondrial energetics, suggesting a pro-death function for MTCH2 during Ca2+-induced injury. Next, we explored the role of BID and MTCH2 in mediating Ca2+-induced injury in primary cortical neurons triggered by prolonged activation of NMDA glutamate receptors. Analysis of intracellular Ca2+ transients, using time-lapse confocal microscopy, revealed that neurons lacking Bid showed markedly reduced Ca2+ levels during the NMDA excitation period. These Ca2+ transients were further decreased when Mtch2 was also silenced. Collectively, our data suggest that BID and MTCH2 functionally interact to promote Ca2+-induced neuronal injury.